Nicotinamide N-methyltransferase: At the crossroads between cellular metabolism and epigenetic regulation - Annalisa Roberti; Agustín F. Fernández; Mario F. Fraga (Elsevier, 2021)
Background: The abundance of energy metabolites is intimately interconnected with the activity of chromatin-modifying enzymes in order to guarantee the finely tuned modulation of gene expression in response to cellular energetic status. Metabolism-induced epigenetic gene regulation is a key molecular axis for the maintenance of cellular homeostasis, and its deregulation is associated with several pathological conditions. Nicotinamide N-methyltransferase (NNMT) is a metabolic enzyme that catalyzes the methylation of nicotinamide (NAM) using the universal methyl donor S-adenosyl methionine (SAM), directly linking one-carbon metabolism with a cell's methylation balance and nicotinamide adenine dinucleotide (NAD+) levels. NNMT expression and activity are regulated in a tissue-specific-manner, and the protein can act either physiologically or pathologically depending on its distribution. While NNMT exerts a beneficial effect by regulating lipid parameters in the liver, its expression in adipose tissue correlates with obesity and insulin resistance. NNMT upregulation has been observed in a variety of cancers, and increased NNMT expression has been associated with tumor progression, metastasis and worse clinical outcomes. Accordingly, NNMT represents an appealing druggable target for metabolic disorders as well as oncological and other diseases in which the protein is improperly activated. Scope of review: This review examines emerging findings concerning the complex NNMT regulatory network and the role of NNMT in both NAD metabolism and cell methylation balance. We extensively describe recent findings concerning the physiological and pathological regulation of NNMT with a specific focus on the function of NNMT in obesity, insulin resistance and other associated metabolic disorders along with its well-accepted role as a cancer-associated metabolic enzyme. Advances in strategies targeting NNMT pathways are also reported, together with current limitations of NNMT inhibitor drugs in clinical use. Major conclusions: NNMT is emerging as a key point of intersection between cellular metabolism and epigenetic gene regulation, and growing evidence supports its central role in several pathologies. The use of molecules that target NNMT represents a current pharmaceutical challenge for the treatment of several metabolic-related disease as well as in cancer.